Economic performance and government size - António Afonso; Jo\~ao Tovar Jalles (European Central Bank (ECB), 2011)
We construct a growth model with an explicit government role, where more government resources reduce the optimal level of private consumption and of output per worker. In the empirical analysis, for a panel of 108 countries from 1970-2008, we use different proxies for government size and institutional quality. Our results, consistent with the presented growth model, show a negative effect of the size of government on growth. Similarly, institutional quality has a positive impact on real growth, and government consumption is consistently detrimental to growth. Moreover, the negative effect of government size on growth is stronger the lower institutional quality, and the positive effect of institutional quality on growth increases with smaller governments. The negative effect on growth of the government size variables is more mitigated for Scandinavian legal origins, and stronger at lower levels of civil liberties and political rights. Finally, for the EU, better overall fiscal and expenditure rules improve growth.
Keywords: C10; C23; H11; H30; O40; 330; common correlated effects; fiscal rules; Growth; institutions; pooled mean group